Caregivers' Attitudes Toward COVID-19 Vaccination in Children and Adolescents With a History of SARS-CoV-2 Infection - Buonsenso, Danilo; Valentini, Piero; Macchi, Marina; Folino, Francesco; Pensabene, Carola; Patria, Maria Francesca; Agostoni, Carlo; Castaldi, Silvana; Lecce, Maurizio; Giannì, Maria Lorella; Marchisio, Paola; Milani, Gregorio P.; et al. (Frontiers in Pediatrics, 2022)
Background Limited data are available on the attitudes of caregivers toward COVID-19 vaccination in children and adolescents with a history of SARS-CoV-2 infection or Long Covid symptoms. The aim of this study was to investigate the vaccine hesitancy among caregivers of children and adolescents with a documented history of SARS-CoV-2 infection and to explore the possible associations between COVID-19 manifestations and the acceptance of the vaccine. Methods Caregivers of children or adolescents with a microbiologically confirmed diagnosis of SARS-CoV-2 infection evaluated in two University Hospitals were interviewed. Results We were able to contact 132 caregivers and 9 declined to participate. 68 caregivers (56%) were in favor of COVID-19 vaccination for their child. In the multiple logistic regression, child's age (OR 1.17, 95%CI 1.06–1.28) and hospitalization due to COVID-19 (OR 3.25, 95%CI 1.06–9.95) were positively associated with being in favor of COVID-19 vaccination. On the contrary, the occurrence of child's Long Covid was associated with a higher likelihood of being against the vaccination (OR 0.28, 95%CI 0.10–0.80). Conclusions This preliminary study shows that only about half of the interviewed parents of children and adolescents with a previous SARS-CoV-2 infection are willing to vaccinate them to prevent a repeated COVID-19 infection. These findings might help healthcare workers to provide tailored information to caregivers of children with a previous SARS-CoV-2 infection.